2013
DOI: 10.1186/1471-2164-14-752
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of AtPAP2 - overexpressing Arabidopsisthalianawith elevated ATP

Abstract: BackgroundAtPAP2 is a purple acid phosphatase that is targeted to both chloroplasts and mitochondria. Over-expression (OE) lines of AtPAP2 grew faster, produced more seeds, and contained higher leaf sucrose and glucose contents. The present study aimed to determine how high energy status affects leaf and root transcriptomes.ResultsATP and ADP levels in the OE lines are 30-50% and 20-50% higher than in the wild-type (WT) plants. Global transcriptome analyses indicated that transcriptional regulation does play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Increased adenylate pools have previously been demonstrated to increase the potato tuber yield in experiments in which the activity of the plastidial adenylate kinase was altered [26]. ATP and adenylate pools were shown to be significantly increased in the rosette leaves of AtPAP2 OE Arabidopsis lines [9]. Meanwhile, the expression levels and enzyme activity of SPS were also significantly elevated in the AtPAP2 OE lines, which could be expected to supply more sucrose for export and anabolism.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Increased adenylate pools have previously been demonstrated to increase the potato tuber yield in experiments in which the activity of the plastidial adenylate kinase was altered [26]. ATP and adenylate pools were shown to be significantly increased in the rosette leaves of AtPAP2 OE Arabidopsis lines [9]. Meanwhile, the expression levels and enzyme activity of SPS were also significantly elevated in the AtPAP2 OE lines, which could be expected to supply more sucrose for export and anabolism.…”
Section: Resultsmentioning
confidence: 87%
“…Primers (Table S1) were designed according to published papers [8] and produce 50‐ to 150‐bp amplicon using Primer5 software. Quantitative RT‐PCR data were corrected by calculation of the PCR efficiency individually using the LinReg PCR software [9].…”
Section: Methodsmentioning
confidence: 99%
“…We assume a similar decoupling of respiratory activity and ADP phosphorylation to occur in pgm roots, as we did not observe phenotypic alterations of roots displaying an elevated ATP/ADP ratio, e.g. increased root/shoot ratio (Carrari et al ., ) or enhanced nitrate uptake (Sun et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Sun et al . () reported that overexpression lines of AtPAP2 contained higher levels of ATP, and the overexpression lines grew faster, produced more seeds, and contained higher concentrations of leaf sucrose and glucose. The higher energy supply may affect the regulation of many transcripts and metabolites which enhance plant growth.…”
Section: Discussionmentioning
confidence: 99%